Identifying Cladribine prescription pattern in MS: an Italian multicentre study - Aurora Zanghì; Roberta Fantozzi; Matteo Foschi; Elisabetta Signoriello; Matilde Inglese; Giacomo Lus; Diego Centonze; Andrea Surcinelli; Tommaso Sirito; Simona Bonavita; Carlo Avolio; Emanuele D’Amico (Therapeutic Advances in Neurological Disorders)
Background: Characterizing Cladribine tablets prescription pattern in daily clinical practice is crucial for optimizing multiple sclerosis (MS) treatment. Objectives: To describe efficacy, safety profile and new disease-modifying therapy (DMT) prescriptions following Cladribine treatment. Design: Independent retrospective cohort study in patients followed at six Italian MS centres. Methods: Patients diagnosed with relapsing MS (RMS) according to 2017 McDonald criteria, who initiated Cladribine between January 2019 and May 2023, were included. A generalized linear regression model was built for the outcome DMT after Cladribine course. Heatmaps were generated based on weighted pivot tables to visualize the proportion of patients requiring DMT post-Cladribine. Results: A total cohort of 352 patients was enrolled, 134 naïve to any DMT, 218 switchers from other DMTs. The last DMT was an injectable first-line DMT for 48 (22%) patients, oral first-line DMT for 141 (64.7%) patients, SP1 inhibitor-Fingolimod for 23 (10.6%) patients, and Natalizumab for 6 (2.7%) patients. Overall, Cladribine was efficacious and well tolerated, 12% of patients required a new DMT prescription after a median time of 24 months. The regression model revealed that patients aged >40 years at Cladribine prescription had a 16% decrease in likelihood of receiving a new DMT. Heatmaps showed patients previously on Fingolimod had a lower rate (72.2%) of being free from therapy after Cladribine. Conclusion: In our multicentric real-world Italian study, Cladribine therapy is generally effective during the investigated follow-up period. Understanding key characteristics of patients responding best to Cladribine can help tailor therapeutic strategies for optimal outcomes.